Legal Implications of Constitutional Court Decision Number 55/PHPU.BPU-XXIII/2025 on the Regional Head Election in North Gorontalo Regency in 2024 - Raikmal Rizki A; Erman I. Rahim; Supriyadi A. Arief (Dalihan Na Tolu: Jurnal Hukum, Politik dan Komunikasi Indonesia, 2026)
This study examines the legal implications of Constitutional Court Decision Number 55/PHPU.BPU-XXIII/2025 on the Regional Head Election in North Gorontalo Regency in 2024. The decision disqualified a candidate pair due to formal deficiencies in the nomination requirements, specifically the status of a convicted person still under probation, and ordered a Re-vote (PSU). Using a normative legal research method with statutory and constitutional approaches, this study finds: first, The construction of the candidacy document verification process for the North Gorontalo regional head election experienced inconsistencies in norm application. The Election Supervisory Body (Bawaslu) employed a comparative approach toward jurisprudence to deliver substantial justice. Meanwhile, the General Election Commission (KPU) positioned itself strictly as an executor to uphold the principle of hierarchical compliance among election organizers ; second, the Constitutional Court Decision resulted in the annulment of KPU Decision Number 1081/2024, disqualification of Candidate Pair Number 3, and a re-vote order within 60 days. Although voter turnout declined by 3.35% in the PSU held on April 19, 2025, public trust in the democratic system as a whole remained relatively intact. This study underscores the importance of strengthening administrative verification mechanisms to ensure electoral integrity.